(untitled) (Acta Entomologica Serbica, 2021)
The occurrence of Dioryctria robiniella in Croatia is confirmed. The species has a disjunct areal in the Mediterranean area of Europe and it is one of the rarer species of its genus. The presence of this species in Croatia has in the literature been noted before, but has recently been excluded from recent checklists of Pyraloidea of Croatia and the Balkan Peninsula. However, the species indeed occurs in the country and has been recorded at seven localities across the coastal areas, from Pag island in the north down to Konavle area in the south, near the border with Montenegro. Further surveys of other neighbouring countries should reveal additional localities for this species in the Balkan peninsula.